1986
DOI: 10.1056/nejm198607103150204
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusNasal Carriage and Infection in Patients on Hemodialysis

Abstract: We conducted a five-year prospective controlled study of prophylaxis of Staphylococcus aureus nasal carriage and infection among patients in a hemodialysis unit. Carriers tended to have chronic colonization with a single phage type. S. aureus infections occurred significantly more frequently in carriers than in noncarriers and, in 93 percent of the infected carriers, were caused by the same phage type as that carried in the nares. Neither intravenous vancomycin nor topical bacitracin was found to be efficaciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
194
4
4

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(219 citation statements)
references
References 27 publications
17
194
4
4
Order By: Relevance
“…Previous studies have identified S. aureus carriage as a risk factor for bacteremia (22,23), but S. aureus carriage did not predict bacteremia in our study. Given the relatively short duration over which isolates were prospectively collected, one of the rationales for the inclusion of isolates associated with bacteremia from the 5-year period prior to the study was to include a potentially more genetically diverse bacterial population from the same setting.…”
Section: Discussioncontrasting
confidence: 97%
“…Previous studies have identified S. aureus carriage as a risk factor for bacteremia (22,23), but S. aureus carriage did not predict bacteremia in our study. Given the relatively short duration over which isolates were prospectively collected, one of the rationales for the inclusion of isolates associated with bacteremia from the 5-year period prior to the study was to include a potentially more genetically diverse bacterial population from the same setting.…”
Section: Discussioncontrasting
confidence: 97%
“…This finding is comparable to the case of chickens with staphylococcal arthritis [15]. In humans, phage-typing studies have revealed that S. aureus strains isolated from sites of infection are often of the same phage type as those present in patients' noses [28].…”
supporting
confidence: 72%
“…However, the use of vancomycin increases the incidence of the vancomycin resistant enterococci 68,69 . Also prophylactic use of rifampicin decreases the incidence of Staphylococcus aureus infection, but its administration is associated with the risk of toxic reactions and with bacterial resistance after short-term administration 70,71 . The perigraft reaction needs to be distinguished from infectious complication.…”
Section: Preventionmentioning
confidence: 99%